Reproducibility of Random Periareolar Fine Needle Aspiration in a Multi-Institutional Cancer and Leukemia Group B (CALGB) Cross-Sectional Study - Ibarra-Drendall, Catherine (2009)
BACKGROUND: Random periareolar fine needle aspiration (RPFNA) is a research technique developed to assess short-term breast cancer risk in women at increased risk of breast cancer. Although there is increasing acceptance of RPFNA, neither the reproducibility nor the inter–institutional compatibility of RPFNA has been established. To address these key limitations, the Cancer and Leukemia Group B (CALGB) Prevention Group tested the reproducibility of RPFNA in a multi-institutional cross-sectional study. METHODS: Sixty-three high-risk women from five CALGB institutions (Duke, Ohio State, Roswell Park, Dana Farber, and Vermont) underwent RPFNA from July 1, 2007 to June 30, 2008. Duplicate bilateral RPFNA was performed on each woman by a single investigator on a single day. Masood Cytology Index score was assessed by a single blinded cytopathologist. RESULTS: There was a high degree of statistical agreement in the Masood Cytology Index scores of duplicate RPFNA samples from the same breast, with a Spearman correlation coefficient of 0.8312 (P < 0.0001). Importantly, although there was agreement in duplicate samples from the same breast, there was lack of agreement between duplicate samples from the opposite breast. CONCLUSIONS: This multi-institutional study shows that RPFNA is a highly reproducible measure of breast cytology in a cooperative group cross-sectional trial. RPFNA did not show a high degree of agreement between breasts, suggesting that breast cancer risk and progression may occur at different rates in individual breasts from a single woman. These studies provide proof-of-principle for future RPFNA-based cooperative group prevention studies.